2012
DOI: 10.1530/eje-11-0972
|View full text |Cite
|
Sign up to set email alerts
|

A stress reaction affects assessment of selectivity of adrenal venous sampling and of lateralization of aldosterone excess in primary aldosteronism

Abstract: Background: A stress reaction involving increased cortisol release, which has not been documented thus far, might affect the assessment of selectivity of catheterization during adrenal venous sampling (AVS). Objective: To investigate whether an ACTH-driven cortisol release occurs during AVS and whether it influences the assessment of selectivity by the step-up of cortisol (plasma cortisol concentrations, PCC) between the adrenal vein blood (PCC SIDE ) and the inferior vena cava (PCC IVC ), e.g. the selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…It showed that a stress reaction (1) occurs in most patients when starting AVS; (2) waned rapidly, usually in less than 15 minutes; (3) increases the SI on both sides at the beginning of the procedure; and (4) is likely to influence also the lateralization index (LI) values when using the sequential AVS. 34 Therefore, the authors concluded that simultaneous catheterization should be preferred, and precautions to minimize stress should be systematically exploited. 34 To the latter end, measures to be adopted both before and during AVS entail explanation of the procedure to the patient, reassurance by the doctor and nurses, and use of benzodiazepines and local anesthesia before venipuncture.…”
Section: Minimizing Stress During Avsmentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that a stress reaction (1) occurs in most patients when starting AVS; (2) waned rapidly, usually in less than 15 minutes; (3) increases the SI on both sides at the beginning of the procedure; and (4) is likely to influence also the lateralization index (LI) values when using the sequential AVS. 34 Therefore, the authors concluded that simultaneous catheterization should be preferred, and precautions to minimize stress should be systematically exploited. 34 To the latter end, measures to be adopted both before and during AVS entail explanation of the procedure to the patient, reassurance by the doctor and nurses, and use of benzodiazepines and local anesthesia before venipuncture.…”
Section: Minimizing Stress During Avsmentioning
confidence: 99%
“…34 Therefore, the authors concluded that simultaneous catheterization should be preferred, and precautions to minimize stress should be systematically exploited. 34 To the latter end, measures to be adopted both before and during AVS entail explanation of the procedure to the patient, reassurance by the doctor and nurses, and use of benzodiazepines and local anesthesia before venipuncture. Allowing the patient to rest quietly for ≥15 minutes before the blood sampling in a friendly environment with psychological assistance can also be useful during the procedure.…”
Section: Minimizing Stress During Avsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ACTH rises in response to stress, however, aldosterone levels may rise transiently in association with apprehension, discomfort, or other stressful stimuli, and this may contribute towards an apparent response to upright posture, or prevent suppression during saline loading. Stress-induced rises in ACTH can cause aldosterone to rise at the start of a procedure such as adrenal venous sampling (AVS), only to fall into a trough during sample collection (463). This may explain some of the occasional instances where the AVS study is unsatisfactory because of the apparent lack of secretion by either gland at the time of sampling (571).…”
Section: Regulation By Acthmentioning
confidence: 99%
“…In fact, the simultaneous catheterization of adrenal veins was proven to provide more reliable results, since more than a half of the patients undergoing AVS present an ACTH-induced stress response, causing an increased cortisol release, which may lead to misinterpretation of the selectivity index when sequential catheterization is used [60].…”
Section: Adrenal Vein Sampling (Avs)mentioning
confidence: 99%